TEACHERS’ BELIEFS AND PRACTICE ON ASSESSMENT IN ENGLISH LANGUAGE TEACHING - Zaenul Wafa (Universitas Pahlawan Tuanku Tambusai, 2021)
Teacher needs to assess the students in the classroom objectively. This study was to explore the teachers’ belief and practice on assessment in English language teaching. The main object of the study concentrated on teachers' beliefs about assessment in MTs Yasis At-Taqwa. Three English teachers participated in this study that consist two certificated and experienced teachers and one novice teacher. The data source of this study were observation, interview, open-ended questionnaire and document analysis. The data validity used was data triangulation to acquire accurate information through multi data sources. The technique to collect data were data reduction, data display and verification. The findings of this study indicated that assessment must cover psychomotor, affective, and cognitive aspect and orientate on the learning process, consider the students’ activeness and attitude. The teachers’ beliefs and practice demonstrate positive relationship between teachers’ beliefs on assessment and classroom practice. The dominant factors that shape teachers’ beliefs and classroom practice reflected in the classroom were school culture, training, teaching experience works best and experience as language learners.